Non nucleoside reverse transcriptase inhibitors, molecular docking studies and antitubercular activity of thiazolidin-4-one derivatives - Chitre, Trupti S.; Patil, Shital M.; Sujalegaonkar, Anagha G.; Asgaonkar, Kalyani D.; Khedkar, Vijay M.; Garud, Dinesh R.; Jha, Prakash C.; Gaikwad, Sharddha Y.; Kulkarni, Smita; Choudhari, Amit; Sarkar, Dhiman (Current Computer-Aided Drug Design, 2019)
Background: Management of Co-existence of Acquired immunodeficiency syndrome and Tuberculosis has become a global challenge due to the emergence of resistant strains and pill burden. Objective: Hence the aim of the present work was to design and evaluate compounds for their dual activity on HIV-1 and Tuberculosis (TB). Methods: A series of seven, novel Thiazolidin-4-one derivatives were synthesized and evaluated for their anti-HIV and anti-tubercular activity along with Molecular docking studies. All the seven compounds displayed promising activity against the replication of HIV-1 in cell-based assays. The four most active compounds were further evaluated against X4 tropic HIV-1(UG)(070) and R5 tropic HIV-1(vB59) primary isolates. The binding affinity of all the designed compounds for HIV-RT and Mycobacterium tuberculosis Enol Reductase (MTB InhA) was gauged by molecular docking studies which revealed crucial thermodynamic interactions governing their binding. Results: The CC50 values for the test compounds were in the range of, 15.08-34.9 mu g/ml, while the IC50 values were in the range of 16.1-27.13(UG(070); X4) and 12.03-23.64 (VB59; R5) mu g/ml. The control drug Nevirapine (NVP) exhibited CC50 value of 77.13 mu g/ml and IC50 value of 0.03 mu g/ml. Amongst all these compounds, compound number 3 showed significant activity with a TI value of 2.167 and 2.678 against the HIV-1 X4 and the R5 tropic virus respectively. In anti-mycobacterial screening, the compounds proved effective in inhibiting the growth of both log phase and starved MTB cultures. Conclusion: Compound 3 has been found to be active against HIV-1 as well as MTB.
Keywords: anti-HIV-1 activity; Antitubercular activity; human immunodeficiency virus-1; Molecular docking; Non nucleoside reverse transcriptase; thiazolidin-4-ones

Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection - Jadaun, Pratiksha; Shah, Prachibahen; Harshithkumar, R.; Said, Madhukar S.; Bhoite, Shubhangi P.; Bokuri, Sowmya; Ravindran, Selvan; Mishra, Neetu; Mukherjee, Anupam (BMC Complementary Medicine and Therapies, 2023)
Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (HR-ESI-MS) technique, followed by the investigation of their potential as anti-HIV-1 and antioxidant agents through in vitro mechanistic assays. The anti-HIV-1 activity was examined in TZM-bl cells through luciferase gene assay against two different clades of HIV-1 strains, whereas the intracellular ROS generation was analyzed by Fluorescence-Activated Cell Sorting. Additionally, the mechanisms of action of these phyto-extracts were determined through the Time-of-addition assay. The characterization of Carica papaya Linn and Psidium guajava leaves extract through HR-ESI-MS fragmentation showed high enrichment of various alkaloids, glycosides, lipids, phenolic compounds, terpenes, and fatty acids like bioactive constituents. Both the phyto-extracts were found to be less toxic and exhibited potent antiviral activity against HIV-1 strains. Furthermore, the phyto-extracts also showed a decreased intracellular ROS in HIV-1 infected cells due to their high antioxidant potential. Overall, our study suggests the anti-HIV-1 potential of Carica papaya Linn and Psidium guajava leaves extract due to the synergistic action of multiple bioactive constituents.
Keywords: anti-HIV-1 activity; Anti-retroviral; Bioactive constituents; Carica papaya Linn; Cytotoxicity; HR-ESI-MS; Psidium guajava; reactive oxygen species